Respuesta :

Answer:

see explanation

Step-by-step explanation:

Using the identity

cos²A - sin²B = cos(A + B) . cos(A - B)

Here A = [tex]\frac{\pi }{8}[/tex] + [tex]\frac{A}{2}[/tex] , B = [tex]\frac{\pi }{8}[/tex] - [tex]\frac{A}{2}[/tex]

Consider the left side

cos²([tex]\frac{\pi }{8}[/tex] + [tex]\frac{A}{2}[/tex] ) - sin²( [tex]\frac{\pi }{8}[/tex] - [tex]\frac{A}{2}[/tex] )

= cos([tex]\frac{\pi }{8}[/tex] + [tex]\frac{A}{2}[/tex] + [tex]\frac{\pi }{8}[/tex] - [tex]\frac{A}{2}[/tex] ) × cos([tex]\frac{\pi }{8}[/tex] + [tex]\frac{A}{2}[/tex] - [tex]\frac{\pi }{8}[/tex] + [tex]\frac{A}{2}[/tex] )

= cos ([tex]\frac{\pi }{4}[/tex] ) × cos ( A)

= [tex]\frac{1}{\sqrt{2} }[/tex] cosA

=  right side , thus proven

ACCESS MORE